Habitat, applications and genomics of the aerobic, thermophilic genus Geobacillus. (1st April 2004) - McMullan, G.; Christie, J.M.; Rahman, T.J.; Banat, I.M.; Ternan, N.G.; Marchant, R.
Abstract : Thermophilic bacteria belonging to Bacillus genetic group 5 have been reclassified as being members of Geobacillus gen. nov., with G. stearothermophilus as the type strain. Geobacillus species, literally meaning earth or soil Bacillus, are widely distributed and readily isolated from natural and man-made thermophilic biotopes. Work within our group has however shown that an abundance of genetically distinct Geobacillus isolates can be obtained from temperate Irish soils. As with many thermophiles there is considerable interest in potential industrial application of these bacteria and their gene products. This review describes two novel applications for Geobacillus isolates, firstly in the metabolism of the herbicide glyphosate and secondly in the metabolism of quorum-sensing signal molecules from Gram-negative bacteria. Finally the current state of the art is described for Bacillus genomics, with details given of three independent genome-sequencing projects of Geobacillus isolates.